The role of HPV gene expression and selected cellular MiRNAs in lung cancer development. (January 2021) - Hussen, Bashdar Mahmud; Ahmadi, Gelavizh; Marzban, Havva; Fard Azar, Maryam Ebadi; Sorayyayi, Saba; Karampour, Romina; Nahand, Javid Sadri; Hidayat, Hazha Jamal; Moghoofei, Mohsen
Abstract: Background: The high mortality rate of lung cancer can be justified that strong need to explore new aspect of tumor biology. Human papillomavirus (HPV) has been detected as risk factor for the development of lung cancer. The aim of this study was to determine the role of HPV and cellular/miRNAs genes expression in the epithelial-mesenchymal transition (EMT) and development of lung cancer. Methods: In this case-control study, 109 lung cancer tissue and 52 controls were included. We analyzed the presence of HPV infection, its genotypes (in positive samples) and the expression of viral genes (E2, E6 and E7). Also, We examined the expression of celluar factors including (a) p53 and retinoblastoma (Rb) (as anti-carcinogenic genes), (b) EMT related genes, (c) selected miRNAs. Results: Our results reported 51.4% and 23.1% of HPV genome in tumor tissues and control tissues samples, respectively. There was a significant association between the HPV positive status and lung cancer (OR = 3.26, 95% C.I = 1.47–7.02, P = 0.001). HPV type 16 was the most prevalent genotype in tissues. The expression of p53, RB, TIMP1, CCNG-1, E-cad and PTPN13 were decreased while MMP-2 and N-cad were increased in HPV-positive tumor/control tissues compared to HPV-negative tissues. Also, among miRNAs, let-7, miR-23, miR-34, miR-125, miR-146 were downregulated and miR-20, miR-424 were upregulated in HPV-positve tissues compared to HPV-negative tissues. Conclusion: This study demonstrated that HPV infection and interaction with cellular genes and miRNAs promote EMT which involved in the lung cancer development. Highlights: N-cad and MMP-2 were significantly upregulated in HPV-positive samples. P53, Rb, TIMP1, CCNG-1, E-cad and PTPN13 were significantly downregulated in HPV-positive samples. miR-20 and miR-424 were upregulated in HPV-positive samples. There was a significant association between HPV infection and lung cancer development. HPV genes and interaction with cellular miRNAs are involved in the lung cancer development.